The Development Strategy Of Sustainable Tourism Village In Conservation Areas And Urban Sprawl (Case Study in Ciburial Village, North Bandung Area) - Maryani, Enok None; Mamat Ruhimat; Dina Siti Logayah (Universitas Negeri Medan, 2025)
Ciburial Village, Cimenyan District, Bandung Regency is located in the North Bandung area, In 1985 it was designated as a tourist village based on agriculture and culture. The purpose of this study to anlyzing the potential and challenges in developing tourism villages with an agricultural and cultural-based approach within conservation areas and regions affected by urban sprawl. The method used is using SWOT analysis. Geographical conditions and strategic position, on the one hand, are very beneficial internally and externally, but on the other hand they are a weakness and a threat. Cool mountain climate and clean air, natural beauty, fertile land, THR (Taman Hutan Raya) Ir. Djuanda, and cultural wealth has the potential to support a sustainable tourism village based on agriculture and culture. On the other hand, it poses a threat due to urban sprawl, very intensive changes in land use, agriculture and forests mutate into settlements, hotels, cafes and other buildings. The existence of the lembang fault, on the one hand, is a threat, on the other hand, it produces cliffs that provide wide and open views in all directions, and is a place for interesting photos for visitors. Internal conditions produce a value of 3.59 and external 3.25, are in quadrant 2 which is stable. The results of this study it is suggested environmental damage needs to be addressed by strictly and consistently implementing provincial regulations. Community-based sustainable tourism village development is an integral part of the tourism village development strategy in Ciburial.